2020
DOI: 10.3390/ijms21176267
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids Toxicity—Benefits and Threats

Abstract: Ionic liquids (ILs) are solvents with salt structures. Typically, they contain organic cations (ammonium, imidazolium, pyridinium, piperidinium or pyrrolidinium), and halogen, fluorinated or organic anions. While ILs are considered to be environmentally-friendly compounds, only a few reasons support this claim. This is because of high thermal stability, and negligible pressure at room temperature which makes them non-volatile, therefore preventing the release of ILs into the atmosphere. The expansion of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(114 citation statements)
references
References 269 publications
(349 reference statements)
1
112
0
1
Order By: Relevance
“…Sorption plays an important role in the toxicity of ILs in the soil [ 73 ]. The results from available studies show that the cations present in ILs with long-chain hydrophobic substitutes can easily adsorb on different types of soil, and become persistent contaminants in the environment [ 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sorption plays an important role in the toxicity of ILs in the soil [ 73 ]. The results from available studies show that the cations present in ILs with long-chain hydrophobic substitutes can easily adsorb on different types of soil, and become persistent contaminants in the environment [ 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the cost and environmental impact (e.g., biodegradability and toxicity) of using ILs as extractants or solvents (for biomass pretreatment) needs to be considered. Despite the overgeneralised idea that ILs are toxic [67][68][69][70][71][72][73], this is not necessarily correct. The toxicity of ILs mainly depends on the length of their alkyl chains, and generalisations that all ILs are toxic are neither straightforward nor supported by recent literature data.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Thus, several studies on the relationship between their molecular structures and toxicity showed that the most toxic (to aquatic life) are those carrying aromatic/heterocyclic cations and long alkyl chains; most anions play a minor role in toxicity. Therefore, the synthesis of a new generation of easily biodegradable ILs and ILBSs from renewable sources was studied [ 36 , 37 , 38 ]. It was shown that ester functionality enhances biodegradation of ILs; furthermore, adding a methyl group to the 2-position of the imidazolium cation and use of alkyl sulfate as a counter-ion also improves the biodegradability [ 36 ].…”
Section: Introductionmentioning
confidence: 99%